Managing the water cycle in Kenyan small‐scale maize farming systems: Part 2. Farmers' use of formal and informal climate forecasts. (2nd November 2015) - Vervoort, R. Willem; Muita, Richard; Ampt, Peter; van Ogtrop, Floris
Abstract : Forecasts can be an important component of water cycle management and farm decision making, particularly where rainfall is uncertain. In Kenya, the use of informal or indigenous forecasting (IF) is known to be widespread, but farmers also use more formal seasonal forecasting (SF) to make decisions in relation to the water cycle. A review of literature indicates that local knowledge is adaptable and often mixes indigenous knowledge and external information. In most cases, IF focusses on more local features and relates more to practical farm activities. Based on extensive interviews and focus groups of farmers in two study areas in Kenya, a majority of farmers from each area used IF, even though SF was also used. There were few farmer characteristics that explained the difference in the use of IF and SF. However, there were differences between the two study areas in how farmers interpreted SF and whether they used a combination of SF and IF. Furthermore there were differences in the local IF indicators used by farmers to identify the onset of the rainy season. To improve the acceptance of SF and increase its use, the information provided in SF needs to be easily incorporated into farmers' current working knowledge, which might also include IF. This means that SF tools should be developed using participatory approaches to ensure the engagement of local farmers. WIREs Water 2016, 3:127–140. doi: 10.1002/wat2.1121 This article is categorized under: Human Water > Water as Imagined and Represented